137k views
5 votes
Let g(x) be the reflection of f(x) = x2 +3 in the x-axis. What is the function rule for g(x)?

A. g(x) = -x2 - 3


B. g(x) = -x2 + 3


C. g(x) = x2 - 3


D. g(x) = x2 + 3

User Taoufik J
by
4.8k points

1 Answer

5 votes

f(x)

a reflection of f(x) in

the x - axist: -f(x)

the y - axist: f(-x)


Therefore


g(x) = -f(x) → g(x) = -(x² + 3) = -x² - 3


Answer: A. g(x) = -x2 - 3

User Canuk
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.